Novel insights into the pathobiology of humoral alloimmune memory in kidney transplantation. Issue 1 (February 2020) - Torija, Alba; Favà, Alex; Meneghini, Maria; Crespo, Elena; Bestard, Oriol
Abstract : Purpose of review: Humoral alloimmunity against human leukocyte antigen (HLA) antigens is the main barrier for successful transplantation. Recent researches have shown that this complex effector immune mechanism is driven by a number of B-cell subsets, which can orchestrate in a perfect and synergistic multistep manner the rejection of the organ transplant. Herein, our purpose is to review the immunobiology of humoral response and discuss novel therapeutic strategies derived from this evidence. Recent findings: Among the distinct cellular components of the humoral alloimmune system, memory B cells (mBC) have been shown to play a key role initiating and maintaining the antidonor humoral alloimmune response, thus its assessment apart from monitoring donor (HLA)-specific antibodies (DSA) in the sera may improve the understanding of the alloimmune status of transplant patients at different time points. Furthermore, targeting alloreactive mBC as well as other B and T-cell counterparts have highlighted for the first time, that novel therapeutic strategies with a more mechanistic rationale are highly warranted for achieving an effective anti-HLA humoral alloimmune control, also in human kidney transplantation. Summary: The complex mechanisms of humoral allorecognitition in transplantation seem to be progressively better understood with the implementation of novel immune technologies. This new insight should serve for the development of novel immunosuppressive strategies to achieve an optimal humoral alloimmune regulation.